The Democratic State - Elkin, Stephen L.; Benjamin, Roger (University Press of Kansas, 1985)
One outcome of the declining economic growth and rising political conflict of the 1980s has been a renewed interest in political theory and increased questioning about the durability of the capitalist state. More and more political scientists are critically assessing the prevailing pluralist vision of the relationships between the state and the economy. Is the capitalist state able to adjust to crises and contradictions? What is the role of the state in changing-deteriorating-economic circumstances? How should we understand competing interpretations on the relative autonomy of the state, the nature of property rights, the legitimation crisis?This collection of five original essays by seven of the bestknown politicaleconomy theorists addresses the interconnections between the economy and the polity and embodies the leading theoretical approaches to the political economy of the state.